(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This study seeks to establish the linguistic roots (Iberian, Celtic, non-Celtic Indoeuropean, Latin) of the ancient place-names of the upper and middle Ebro valley. The etymology of the names of mountains, rivers and towns attested in sources of the Roman period is re-examined, resulting in important conclusions on the different layers that make up the region’s linguistic profile. The largest group of toponyms is Indoeuropean, representing 37% of the total, followed by Celtic (33%) and Iberian (10%). The small proportion of Latin names (8% of the total) reflects the limited impact of Romanization in this zone.